ARG16GLY POLYMORPHISM IN THE Β2-ADRENOCEPTOR GENE IN PATIENTS WITH BRONCHIAL ASTHMA WITH REGARD TO THE AGE OF ONSET - Kachkovska, V.V.; Prystupa, L.N.; Orlovskyi, V.F. (World of Medicine and Biology, 2023)
The frequency of Arg16Gly polymorphism in the β2-adrenoceptor gene was studied in 553 patients with bronchial asthma depending on the age of onset: in 282 patients with late onset of asthma and 271 patients with early onset. Also, the study included 95 healthy individuals. In the late-onset asthma group Arg/Arg genotype was present in 35.8 %, Arg/Gly genotype – in 52.5 %, Gly/Gly genotype – in 11.7 % of patients, while in the early-onset asthma group, it was present in 26.6; 38.7 and 34.7 % of patients, respectively (χ2=41.26; р=0.001). We observed an increased risk of developing early-onset asthma: it was 2.83 times higher (p=0.001) in the recessive model and 1.87 times higher (p=0.001) in the additive model vs. the major allele homozygotes. No association was found with the risk of late-onset asthma. Gly allele carriers, both heterozygotes, and the minor allele homozygotes have an increased risk of developing early-onset bronchial asthma rather than late-onset asthma.